Empathy and Delight in a Personal Service Setting*. Issue 1 (February 2020) - Nguyen, Thi Nguyet Que; Tran, Quan Ha Minh; Chylinski, Mathew
This study examines the mechanisms through which employee empathy is related to customer delight in a personal service setting where customers and frontline employees interact to produce and deliver a service. Building on trait-behavior-performance relation, we propose that there exists an indirect relationship between employee empathy and customer delight with the employee, and that employee deep acting and perceived service quality would independently and serially mediate the empathy-satisfaction relationship. Health care is an appropriate context for examining the role of empathy in customer-employee interactions because of the depth and variance of service experiences. Our sample includes 154 dyads of customers (patients) and service employees (doctors), who were surveyed after a patient and a doctor completed a health consultation, diagnosis or treatment. Our findings suggest that special attention should be paid to leverage deep acting and empathy dimensions of health care. Specifically, health care managers should concentrate on the improvement of competency and capability of medical employees and establishment of a sincere and authentic relationship between patients and employees to achieve patient delight.